Odpowiedź :
a)
[tex]3\frac{3}{4} -1\frac{1}{4} :\frac{5}{6} =2\frac{2}{4} :\frac{5}{6} =\frac{10}{4} *\frac{6}{5} =\frac{2}{2} *\frac{3}{1} =\frac{6}{2} =3[/tex]
Jest to:
[tex]\frac{3}{35}[/tex]
b)
[tex](2\frac{1}{3} -1 \frac{3}{4} ):\frac{7}{8} =(2\frac{4}{12}-1\frac{9}{12} ):\frac{7}{8} =(1\frac{16}{12}-1\frac{9}{12} ):\frac {7}{8}=\frac{7}{12}*\frac{8}{7}=\frac{1}{3} *\frac{2}{1} =\frac{2}{3}[/tex]
Jest to
[tex]\frac{2}{3} :35=\frac{2}{3} *\frac{1}{35} =\frac{2}{105}[/tex]
Myślę że pomogłem ;)